2021
DOI: 10.1029/2021jc017257
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Diapycnal Mixing in the Indian Ocean

Abstract: The rate of turbulent kinetic energy dissipation and diapycnal diffusivity are estimated along 10 hydrographic sections across the Indian Ocean from a depth of 500 m to the seabed. Six sections were occupied twice. On the meridional section, which is nominally along 95°E, spatial patterns were observed to persist throughout the three occupations. Since the variability in diffusivity exceeds the variability in the vertical gradients of temperature and salinity, we conclude that the diffusive diapycnal fluxes va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The present large h 0 is consistent with the averaged vertical profiles of K ρ inferred from strain‐based finescale parameterizations (Kunze, 2017) and the empirical model based on finescale parameterizations (Katsumata et al., 2021) and from the FP07 observation (Goto et al., 2021). This could be partly because the present empirical model does not involve the data near the bottom between seafloor and the 160 m above bottom, and the vertical average of 320 m might erase the structure near the bottom and instead emphasize the large vertical scale impact from fine horizontal scale rough bottom topography.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The present large h 0 is consistent with the averaged vertical profiles of K ρ inferred from strain‐based finescale parameterizations (Kunze, 2017) and the empirical model based on finescale parameterizations (Katsumata et al., 2021) and from the FP07 observation (Goto et al., 2021). This could be partly because the present empirical model does not involve the data near the bottom between seafloor and the 160 m above bottom, and the vertical average of 320 m might erase the structure near the bottom and instead emphasize the large vertical scale impact from fine horizontal scale rough bottom topography.…”
Section: Discussionsupporting
confidence: 87%
“…By summarizing the relationships between above‐mentioned variables (N2 ${\overline{N}}^{2}$, var(bH), ( U ) mean ) and ε FP 07 or K ρ , we here attempt to empirically formulate the observed ε FP 07 or K ρ as a function of those variables (N2 ${\overline{N}}^{2}$, var(bH), ( U ) mean ), focusing here on the bottom topographic influence as previously attempted (e.g., Decloedt & Luther, 2010; Katsumata et al., 2021). In the present study, the observed diffusivity K ρ is almost independent on N2 ${\overline{N}}^{2}$ ( R = −0.10) as assumed in the previous study (Decloedt & Luther, 2010), which is consistent with the model of Henyey et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This scheme provides a reliable basis for calculating the turbulent mixing below the mixing layer by using the temperature and salinity profiles obtained from Argo floats. This parameterization scheme was successfully applied in various regions, such as the Northwestern Pacific (Whalen et al., 2018) and the Indian Ocean (Katsumata et al., 2021), to accurately describe the spatial and temporal distributions of turbulent mixing and was found to be consistent with the observations from microstructure data. Therefore, the finescale parameterization scheme can reasonably derive diapycnal turbulent mixing.…”
Section: Finescale Parameterizationsmentioning
confidence: 69%